Protocol for the development and acceptability of a fertility-related decision aid for young women with breast cancer in Portugal - Vânia Gonçalves; Luzia Travado; Pedro Lopes Ferreira; Gwendolyn Quinn (BMJ Open)
Introduction Young patients with breast cancer may face impaired fertility due to cancer treatments, which often leads to complex fertility decisions. To aid fertility decision-making, it is crucial that women have access to high-quality information; however, their fertility information needs are often unmet. Decision aids (DAs) are educational materials to assist with decision-making, by addressing individual values and preferences. In oncofertility, DAs may constitute a valuable resource to help patients obtain information and make better informed decisions. This paper reports on the protocol of the development and transcreation of a fertility-related DA booklet to support young Portuguese patients with breast cancer, originally developed and validated for an Australian audience.Methods and analysis Recent literature on clinical guidelines will be reviewed. A summary of these guidelines will be created and will inform the first round of DAs revisions. A forward translation process will translate the DA from Australian English to Portuguese. A multidisciplinary Portuguese experts panel will revise and give feedback on the scientific and cultural aspects of the DA content for Portuguese audience. Next, a backward translation process will assess content equivalence between the original and the final adapted version. Finally, Learner Verification (LV) will be used in a qualitative study of young patients with breast cancer and their partners. Two focus groups with 6–10 participants each will be conducted with: (1) recently diagnosed young patients with breast cancer; (2) breast cancer survivors and (3) their partners. Results from the DA acceptability assessment will inform its final version. Data will be analysed using content analysis and constant comparison method to identify key themes/textual units related to LV.Ethics and dissemination Ethical approval was granted by the Portuguese Institute of Oncology Porto. Results will be disseminated through peer-reviewed journals and presented at scientific meetings for academic and health professionals audiences.